A Review and Critique of the Collection of Iranian Poetry by Vlimir Khelebnikov, Russian Futurist - Zeinab Sadeghi Sahlabad; Mahboubeh Mobasheri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of the present study is to show the influence of Iranian culture and literature on another territory. Russian futurist, Vlimir Khelebnikov (1922-1884), was one of those poets who greatly influenced Iranian culture and literature. He was one of the Russian poets who had the chance to be present in Iran and came to Gilan during the uprising of Mirza Kochak Khan along with the Red Army forces in Gilan and was able to get acquainted with Iran. Orientalism is one of the most prominent aspects of his poetry, in which we will only examine the themes of his six-volume collection of poems in the present study. The re-creation of Iranian themes with new manifestations in his poetry has rendered Khelebnikov’s poetry beautiful and exquisite. Although Iran’s influence on him is not limited to literary and mythical aspects of Iran and beyond, it can be examined in cultural, religious, historical, and biological and natural dimensions, But Iranian scholars have paid little attention to his work. An examination of Khelebnikov’s poetry reveals his love for Hakim Ganjeh and reflects on his military poems as well as Shahnameh’s myths.